Pelatihan Andragogi untuk Meningkatkan Literasi Bisnis Multi-Level Marketing Ibu Rumah Tangga Jabodetabek - Derah Sudjaniah (Penerbit Goodwood, 2026)
Purpose: This community service program aimed to enhance housewives’ understanding of Multi-Level Marketing (MLM) as an alternative strategy to support family income. Methodology/approach: The training was conducted in the Jabodetabek area in September 2024 using a combination of lectures, group discussions, and simulations. The modules covered MLM fundamentals, ethics and legality, simple financial management, and basic product marketing. A total of 98 housewives participated. Knowledge improvement was measured using pre-test and post-test assessments. Results/findings: Findings show a significant increase in participants’ understanding, with an average knowledge improvement of approximately 80% after the training. Participants demonstrated better ability to distinguish legal from illegal MLM schemes, record simple household finances, and apply introductory digital marketing strategies. More than half of the participants developed personal business action plans as follow-up steps. Conclusions: Structured andragogical training effectively improves business literacy among adult learners, particularly housewives who seek additional income. The program shows that practical, experience-based learning can enhance entrepreneurial readiness in community settings Limitations: This study was limited to the Jabodetabek region and involved only housewives, so the findings may not be generalizable to other demographic groups. Contributions: This study provides evidence that targeted community training strengthens MLM literacy, boosts motivation for entrepreneurship, and supports family economic resilience. It contributes to community empowerment studies and entrepreneurship education by demonstrating the impact of applied adult learning strategies.